2011
DOI: 10.3390/molecules16066378
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacities and Total Phenolic Contents Increase with Gamma Irradiation in Two Types of Malaysian Honey

Abstract: Two types of monofloral Malaysian honey (Gelam and Nenas) were analyzed to determine their antioxidant activities and total phenolic and flavonoid contents, with and without gamma irradiation. Our results showed that both types of honey can scavenge free radicals and exhibit high antioxidant-reducing power; however, Gelam honey exhibited higher antioxidant activity (p < 0.05) than Nenas honey, which is in good correlation (r = 0.9899) with its phenolic contents. Interestingly, we also noted that both irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 50 publications
7
54
0
1
Order By: Relevance
“…The work documented here is an extension to our previous work in colon adenocarcinoma cell line HT 29 where, we found that Gelam honey exhibited higher chemopreventative effects on HT 29 colon cancer cell line than Nenas honey by inducing apopotosis and suppressing inflammation possibly through its antioxidant property (Wen et al, 2012). These two types of Malaysian honeys have been reported earlier having their antioxidant activities significantly correlated to the content of the phenolic compounds (Hussein et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…The work documented here is an extension to our previous work in colon adenocarcinoma cell line HT 29 where, we found that Gelam honey exhibited higher chemopreventative effects on HT 29 colon cancer cell line than Nenas honey by inducing apopotosis and suppressing inflammation possibly through its antioxidant property (Wen et al, 2012). These two types of Malaysian honeys have been reported earlier having their antioxidant activities significantly correlated to the content of the phenolic compounds (Hussein et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…Our fi ndings are similar with the results obtained by YAO and co-workers (2011), where DNA damage was found to decrease signifi cantly with Gelam honey supplementation. Our results also support previous studies, which claimed that Nenas honey has the ability to scavenge free radicals (HUSSEIN et al, 2011;KISHORE et al, 2011). Quercetin, which is the second most abundant fl avonoid in Nenas honey, prevents DNA damage by incorporating into the red blood cells structure to provide defence and promote cell function (ALVAREZ-SUAREZ et al, 2012).…”
Section: Dna Damagesupporting
confidence: 80%
“…Our results were in agreement with the earlier studies of Mishra et al (2011), who reported that the flavonoid content marginally increased during low temperature storage for 30 days in irradiated and control sugarcane juice samples. Hussein et al (2011) also reported that two types of irradiated Malaysian honey exhibited a significantly (P<0.05) higher content of flavonoids than their non-irradiated counterparts. Effect of γ-irradiation on the content of individual polyphenolic compounds of mango juice There were significant (P<0.05) differences noted in the concentration of polyphenolic compounds between nonirradiated and irradiated juice samples (Table 3).…”
Section: Microbial Quality Of Mango Juicementioning
confidence: 95%
“…It can be postulated that the increase in antioxidant activities following γ-irradiation could be due to the degradation of some high molecular weight polymeric phenolic compounds to simple phenols thus enhancing their solubility in the test solvent resulting in greater interaction with the reagents. Hussein et al (2011) reported increased antioxidant activities, resulting from higher polyphenol and flavonoid content in γ-irradiated honey samples. The antioxidant capacities of γ-irradiated and control juice samples using FRAP assay is shown in Table 4.…”
Section: In Vitro Antioxidant Capacitiesmentioning
confidence: 99%